Nanomechanical properties of single protein molecules and peptides - Ploscariu, Nicoleta T. (Kansas State University, 2014)
Proteins are involved in many of the essential cellular processes, such as cell adhesion, muscle function, enzymatic activity or signaling. It has been observed that the biological function of many proteins is critically connected to their folded conformation. Thus, the studies of the process of protein folding have become one of the central questions at the intersection of biophysics and biochemistry. We propose to use the changes of the nanomechanical properties of these biomolecules as a proxy to study how the single proteins fold. In the first steps towards this goal, the work presented in this thesis is concentrated on studies of unfolding forces and pathways of one particular multidomain protein, as well as on development of the novel method to study elastic spring constant and mechanical energy dissipation factors of simple proteins and peptides. In the first part of this thesis we present the results of the mean unfolding forces of the NRR region of the Notch1 protein. Those results are obtained using force spectroscopy techniques with the atomic force microscope (AFM) on a single molecule level. We study force-induced protein unfolding patterns and relate those to the conformational transitions within the protein using available crystal structure of the Notch protein and molecular dynamics simulations. Notch is an important protein, involved in triggering leukemia and breast cancers in metazoans, i.e., animals and humans. In the second part of this thesis we develop a model to obtain quantitative measurements of the molecular stiffness and mechanical energy dissipation factors for selected simple proteins and polypeptides from the AFM force spectroscopy measurements. We have developed this model by measuring the shifts of several thermally excited resonance frequencies of atomic force microscopy cantilevers in contact with the biomolecules. Next, we provided partial experimental validation of this model using peptide films. Ultimately, our results are expected to contribute in the future to the developments of medical sciences, which are advancing at a level, where human health and disease can be traced down to molecular scale.
Keywords: Atomic Force Microscopy; Protein; Peptide; nanomechanical properties; Biomechanics (0648); Biophysics (0786); Condensed Matter Physics (0611); Molecular Biology (0307); Physics (0605)